Determination of Cerebrovascular Reactivity by Means of fMRI Signal Changes in Cerebral Microangiopathy: A Correlation with Morphological Abnormalities - Hund-Georgiadis, Margret; Zysset, Stefan; Naganawa, Shinji; Norris, David G.; von Cramon, D. Yves (Cerebrovascular diseases (Basel, Switzerland), 2003)
Background and Purpose: A reduced cerebrovascular reactivity (CR) is a risk factor of cerebrovascular disease. In this study, we implemented a protocol to assess CR by means of functional MRI (fMRI) using hyperventilation. Subjects and Methods: In 5 patients with cerebral microangiopathy (CM/lacunar infarction and white matter degeneration), 6 healthy elderly subjects (age-matched control), and 6 young healthy subjects, the CR in response to hyperventilation was evaluated by fMRI using gradient echo-planar Imaging. The percentage signal change normalized by end-tidal CO 2 value was measured in various brain regions. Results: All subjects performed hyperventilation well without adverse reaction and significant gross motion. Patients with CM showed significant qualitative and quantitative differences (p < 0.05) as compared to controls. The volume of gray matter showing significant CR was significantly reduced in patients: by 40% in comparison to the age-matched elderly control group and by 60% when compared with the young controls. The CR impairment was most pronounced in the frontal cortices with a drastically reduced magnitude of the magnetic resonance (MR) signal change in the patients (–0.62 ± 0.2% in patients versus –2.0 ± 0.36% in age-matched controls, p < 0.0001). A strong relation was evident between the fMRI-based CR reduction in patients with CM and the individual severity of structural MR abnormalities (p = 0.002). Conclusion: This study demonstrates that fMRI-based signal changes in response to hyperventilation reliably reflect cerebral vasoreactivity. The protocol is feasible in healthy young and elderly controls and patients with CM. Quantitative and qualitative assessment of the signal decrease in the T 2 -weighted MR sequence and coregistration with individual anatomical data allow the generation of an individual cerebral vasoreactivity map. Future research will address the effect of CR reduction on neuropsychological parameters in patients with CM.